Proteomic compensation by paralogs preserves protein interaction networks after gene loss in cancer - Anjan Venkatesh; Niall Quinn; Swathi Ramachandra Upadhya; Barbara De Kegel; Alfonso Bolado Carrancio; Thomas Lefeivre; Olivier Dennler; Kieran Wynne; Alexander von Kriegsheim; Colm J Ryan (Molecular Systems Biology)
Abstract Proteins operate within dense interconnected networks, with interactions necessary both for stabilising proteins and enabling them to execute their molecular functions. Remarkably, protein–protein interaction networks operating within tumour cells continue to function despite widespread genetic perturbations. Previous work has demonstrated that tumour cells tolerate perturbations of paralogs better than perturbations of singleton genes, but the underlying mechanisms remain poorly understood. Here, we systematically profile the proteomic response of tumours and cell lines to gene loss. We find many examples of proteomic compensation, where loss of one gene causes increased abundance of a paralog, and collateral loss, where gene loss causes reduced paralog abundance. Compensation is enriched among paralog pairs that are central in the protein–protein interaction network and whose interaction partners perform essential functions. Compensation is also significantly more likely to be observed between synthetic lethal pairs. Our results support a model whereby loss of one gene results in increased protein abundance of its paralog, stabilising the protein–protein interaction network. Consequently, tumour cells may become dependent on the paralog for survival, creating potentially targetable vulnerabilities.